2020
DOI: 10.1080/2156857x.2020.1806102
|View full text |Cite
|
Sign up to set email alerts
|

The role of social support for social workers engaged in preventing radicalization and violent extremism

Abstract: Over the last decade, social workers have been engaged in prevention work against violent extremism in the United Kingdom and the Nordic countries. There are scholarly findings of professional uncertainty among social workers carrying out this task, but the influence of organizational factors and support have not yet been studied in this context. This paper fills some of that gap with findings from research using 17 in-depth and two focus group interviews with experienced social workers involved in prevention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(39 citation statements)
references
References 55 publications
(87 reference statements)
0
39
0
Order By: Relevance
“…By this stage, basic knowledge on radicalization and MI had been disseminated across local actors in Eastern Norway and beyond, but there were still gaps and considerable variations across municipalities. Measures introduced against RVE in the preceding phases had, however, helped establish radicalization and Islamist extremism as new social problems that were now much more likely to be recognized by frontline personnel in schools, social welfare and other public agencies (e.g., Haugstvedt, 2019). Training, increased knowledge and systematic educational efforts also seem to have contributed to greater confidence among frontline personnel and those with key coordination roles about how they should understand and approach militant Islamism in their local areas.…”
Section: From Escalation To De-escalation: Five Phases Of Development In the Plural Policing Of Militant Islamismmentioning
confidence: 99%
“…By this stage, basic knowledge on radicalization and MI had been disseminated across local actors in Eastern Norway and beyond, but there were still gaps and considerable variations across municipalities. Measures introduced against RVE in the preceding phases had, however, helped establish radicalization and Islamist extremism as new social problems that were now much more likely to be recognized by frontline personnel in schools, social welfare and other public agencies (e.g., Haugstvedt, 2019). Training, increased knowledge and systematic educational efforts also seem to have contributed to greater confidence among frontline personnel and those with key coordination roles about how they should understand and approach militant Islamism in their local areas.…”
Section: From Escalation To De-escalation: Five Phases Of Development In the Plural Policing Of Militant Islamismmentioning
confidence: 99%
“…Notably absent from this recent scholarship on PVE are US social work academics, with a few exceptions (e.g., Hutson et al, 2009 ; Ellis & Abdi, 2017 ). However, some sound critiques and discussions in the literature on social work in countering terrorism from European social work scholars (e.g., Finch et al, 2019 ; Haugstvedt, 2019 ; McKendrick & Finch, 2017 ). This scholarship has often been critical of the underlying assumptions of the prevention models that target youth deemed at risk, for example, the PREVENT/Channel program in the United Kingdom (UK) (Awan & Guru, 2017 ; Stanley et al, 2018 ; Stanley & Guru, 2015 ; Guru, 2010 ).…”
Section: Brief History Of Violent Extremism Prevention Approaches Since 9/11mentioning
confidence: 99%
“…Further, while associated with right-wing lone wolf attacks, mental health is not a primary driver of most forms of radicalization. Social workers in Norway, for example, were found to treat potentially radicalized youth as they would any social problem (Haugstvedt, 2019 ). Unfortunately, what is ignored in this scholarship is reference to specific, empirically validated social work prevention models that appear to have direct applicability to PVE.…”
Section: Social Work Engagement In Pve: a Call To Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, risk signals of violent extremism are too abstract for the youth workers to be able to conduct PVE work (Van de Weert and Eijkman 2019). In his study of Norwegian social workers, Haugstvedt (2019) found that they understand radicalization as a social problem and go about their work with that perspective. According to Haugstvedt (2019), gaining trust is imperative for being able to conduct PVE work, but that is the case with all forms of social work.…”
Section: Firstline Professionals and Prevention Of Violent Extremismmentioning
confidence: 99%